PERAN PEMERINTAH DALAM PENGATURAN TERHADAP PENETAPAN SUKU BUNGA PINJAMAN KOPERASI SIMPAN PINJAM (Studi di Kota Pontianak) - NIM. A1012171151, WING PATRIO (Jurnal Fatwa Hukum, 2024)
ABSTRACT  Currently, many savings and loan cooperatives have emerged that offer loans (credit) to their members and the community at large. In offering loans, savings and loan cooperatives provide interest to cooperative members and the community. The loan interest rates provided by savings and loan cooperatives have so far referred to the provisions of the Decree of the Minister of State for Cooperatives, Small and Medium Enterprises Number 96/KEP/M.KUKM/IX/2004 concerning Operational Standards Guidelines for the Management of Savings and Loan Cooperatives and Cooperative Savings and Loan Units. market mechanism, so there is no clear standard regarding interest rates for savings and loan cooperative loans. In practice, the loan interest rates applied by Savings and Loans Cooperatives to members and the public can reach 30% per month. The provision of high interest rates by savings and loan cooperatives is of course very burdensome for their members or the community. The research method used in this research is sociological juridical and analytical descriptive. The data examined in this research includes primary data and secondary data. Data collection techniques include: literature study, interviews, and questionnaires. The data analysis method used in this research is qualitative analysis. Based on the research results, it was concluded that the interest rate given by the Savings and Loans Cooperative in Pontianak City to its members is between 20% to 30% per month with a loan term of 30 days/month. In reality, the Government has not actually played a role in regulating the interest rates for Savings and Loans Cooperative as an effort to improve the welfare of its members and the community because until now there are no regulations regarding the determination of interest rates for Savings and Loans Cooperatives. Only on June 16 2023, the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia issued Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 8 of 2023 concerning Savings and Loans Businesses by Cooperatives, which regulates the loan interest rate at a maximum of 24% (twenty four percent) per year, but the practice of giving loan interest rates between 20% to 30% per month carried out by the Savings and Loans Cooperatives is still ongoing today and there has been no action from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, the Regional Indonesian Cooperative Council and the Provincial and Regency/City Cooperative Services regarding the Savings and Loans Cooperative. The impact resulting from the absence of regulation on the determination of interest rates for savings and loan cooperative loans is that Savings and Loans Cooperatives provide high interest rates, even exceeding bank interest rates, and give rise to the practice of loan sharks under the pretext of Savings and Loans Cooperatives.  Keywords: Role, Government, Regulation, Determination, Interest Rates, Loans, Cooperatives.  A B S T R A K  Saat ini banyak bermunculan koperasi simpan pinjam yang menawarkan pinjaman (kredit) kepada anggotanya maupun masyarakat secara luas. Dalam menawarkan pinjaman, koperasi simpan pinjam memberikan bunga kepada anggota koperasi maupun masyarakat. Suku bunga pinjaman yang diberikan oleh koperasi simpan pinjam selama ini mengacu pada ketentuan Keputusan Menteri Negara Koperasi, Usaha Kecil dan Menengah Nomor 96/KEP/M.KUKM/IX/2004 Tentang Pedoman Standar Operasional Manajamen Koperasi Simpan Pinjam dan Unit Simpan Pinjam Koperasi adalah menggunakan mekanisme pasar, sehingga tidak ada standard yang jelas mengenai suku bunga pinjaman koperasi simpan pinjam. Dalam praktiknya, pemberian suku bunga pinjaman kepada anggota maupun masyarakat yang diberlakukan oleh Koperasi Simpan Pinjam bisa mencapai 30% per bulan. Pemberian suku bunga yang tinggi oleh koperasi simpan pinjam tentu saja sangat memberatkan bagi anggotanya atau masyarakat. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis sosiologis dan bersifat Deskriptif Analitis. Data yang diteliti dalam penelitian ini meliputi data primer dan data sekunder. Teknik pengumpulan data yang meliputi: studi kepustakaan, wawancara, dan kuesioner (angket). Metode analisis data yang digunakan dalam penelitian ini adalah analisis kualitatif. Berdasarkan hasil penelitian, maka diperoleh kesimpulan bahwa besaran suku bunga yang diberikan Koperasi Simpan Pinjam (KSP) di Kota Pontianak kepada anggotanya antara 20% hingga 30% per bulan dengan jangka waktu pinjaman selama 30 hari/sebulan. Dalam kenyataannya, Pemerintah sebenarnya belum berperan dalam pengaturan terhadap penetapan suku bunga pinjaman Koperasi Simpan Pinjam (KSP) sebagai upaya untuk mensejahterakan anggotanya dan masyarakat karena hingga saat ini belum ada regulasi mengenai penetapan suku bunga pinjaman Koperasi Simpan Pinjam (KSP). Baru pada tanggal 16 Juni 2023, Menteri Koperasi dan Usaha Kecil dan Menengah Republik Indonesia menerbitkan Peraturan Menteri Koperasi dan Usaha Kecil dan Menengah Republik Indonesia Nomor 8 Tahun 2023 tentang Usaha Simpan Pinjam Oleh Koperasi, yang mengatur Suku bunga Pinjaman paling tinggi 24% (dua puluh empat persen) per tahun, tetapi praktik pemberian suku bunga pinjaman antara 20% sampai dengan 30% per bulan yang dilakukan oleh Koperasi Simpan Pinjam (KSP) ini masih tetap berlangsung sampai sekarang dan tidak ada tindakan dari Kementerian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia, Dewan Koperasi Indonesia Daerah (DEKOPINDA) maupun Dinas Koperasi di Provinsi dan Kabupaten/Kota terhadap Koperasi Simpan Pinjam (KSP) tersebut. Dampak yang ditimbulkan dari tidak adanya pengaturan terhadap penetapan suku bunga pinjaman koperasi simpan pinjam adalah Koperasi Simpan Pinjam (KSP) memberikan suku bunga yang tinggi, bahkan melebihi suku bunga bank, dan menimbulkan praktik rentenir dengan dalih Koperasi Simpan Pinjam (KSP).  Kata Kunci:           Peran, Pemerintah, Pengaturan, Penetapan, Suku Bunga, Pinjaman, Koperasi.